An unusual and severe cutaneous presentation of multisystem Langerhans cell histiocytosis. - Sadhwani, M.; Kulkarni, V.; Patki, A.; Kanvinde, S. (European Journal of Pediatric Dermatology, 2025)
Langerhans cell histiocytosis (LCH) is characterized by the proliferation of Langerhans cells in the skin and/or various internal organs. In infants it often presents with skin lesions, ranging from a seborrheic dermatitis-like picture to nodules and plaques. In the current report we describe a case of multisystem LCH in a three-month-old child, who initially presented with ulcerated and crusted cutaneous lesions on the head and trunk. A comprehensive analysis was essential to arrive at the diagnosis. The child responded well to chemotherapy.